(untitled) (Annals of Medical Research, 2024)
Aim: Given that metformin is often recommended for the management of type 2 diabetes mellitus, it is clinically significant to consider the potential interactions between metformin and other medications. In this study, we aimed to identify potential drug-drug interactions associated with metformin by retrospectively analyzing the prescriptions of patients taking metformin. Materials and Methods: Metformin-containing prescription data of five independent community pharmacies in Konya province for the year 2023 were analyzed retrospectively. Medscape®, Drugs® and LexiComp® software programs were used to detect potential drug-drug interactions. As a result of power analysis with the G Power program, 400 patients were included in the study with an effect size of 0.25, type 1 error of 0.05 and confidence interval of 0.95. Results: Kendall’s W value indicating the agreement between Medscape®, Drugs® and LexiComp® software programs was calculated as 0.061. In terms of potential drug-drug interactions of metformin, the agreement between the software programs was observed to be slight. The highest agreement between the progrmas was observed between Medscape® and LexiComp® (Kappa coefficient=0.44). Conclusion: Since potential drug-drug interactions are common in prescriptions for patients taking metformin, these interactions should be carefully monitored. Clinicians should use multiple interaction programs to identify potential drug-drug interactions of metformin.